Antibody-Drug Conjugates in the Treatment of Metastatic Breast Cancer: The Emerging Questions of Sequence and Resistance - Allan Relecom; Francesco Sciotto; Mathieu Chevallier; José Luis Sandoval (healthbook TIMES. Oncology Hematology)
Metastatic breast cancer continues to present significant therapeutic challenges, necessitating ongoing exploration of innovative treatments. The use of antibody-drug conjugates (ADCs) represents an effective treatment strategy that combines the targeting capabilities of monoclonal antibodies with the cytotoxic effects of chemotherapeutic agents to deliver therapy directly to cancer cells. This article reviews recent advancements and the efficacy of ADCs in clinical trials and explores the mechanisms of resistance and the implications of ADC sequencing in treatment protocols.